The Relationship of Environmental Sanitation and Family Attitudes with Events of Dengue Hemorrhagic Fever (DHF) in Working Areas UPTD Public Health Centre Bendo Kediri District - Ahmad Wasis Setyadi; Astri Yunita; Nanang Muhibuddin (Journal for Quality in Public Health, 2021)
in Indonesia. The increase in dengue cases every year is related to poor environmental sanitation. The purpose of this study was to determine the relationship of environmental sanitation and family attitudes with the incidence of dengue in the working area of ​​UPTD Puskesmas Bendo, Kediri Regency, 2019. The design was correlational analytic research with cross sectional approach. The population of the entire community working area UPTD Puskesmas Bendo District of Kediri diagnosed with DHF as many as 30 families with a sample of 30 respondents taken a total sampling. The independent variable was environmental sanitation and attitude, the dependent variable was dengue collected by questionnaire and checklist and analyzed by Mc Nemar test and Linear Regression. To the p = <0.05 then H0 is rejected and p => 0.05 then H0 is accepted. Environmental sanitation with the incidence of DHF (p = 0.031). Family attitudes with the incidence of DHF (p = 0.039). Environmental sanitation and family attitudes with the incidence of DHF in the Work Area of ​​UPTD Puskesmas Bendo, Kediri Regency in 2019 (p = 0.110). It was concluded that there was a relationship between environmental sanitation and the incidence of DHF, there was a relationship between family attitudes and the incidence of DHF and there was no relationship between environmental sanitation and family attitudes with the incidence of DHF. So that people are more concerned about environmental sanitation to reduce the occurrence of dengue fever as a manifestation of the movement of one house 1 cadre of jumantik.